The problem of meaning in the dialogue between science and religion (2019)
This paper critically explores the thesis according to which the main difference between science and religion is that while the former seeks to explain the causal order of the world, the latter deals with giving meaning to the totality of what exists and to individual experiences and actions. In the first part, it shows that explaining and giving meaning are solidarity endeavours, which cannot be easily separated either in science or in religion. Likewise, it finds the central issue of the dialogue between both domains in the question of the origin of meaning. In the second part, it argues against the social constructionist assumption according to which all meanings are entirely a human product. Finally, some aspects are pointed out about which the sciences and Christianity can talk about the existence of transcendent meaning in both nature and human life. © 2018.Este trabajo explora críticamente la tesis según la cual la diferencia central entre ciencia y religión consiste en que, mientras que aquella busca explicar el orden causal del mundo, esta se ocupa de dar sentido a la totalidad de lo que existe y a las experiencias y acciones individuales. En la primera parte se muestra que explicar y dar sentido son empresas solidarias que no pueden separarse fácilmente ni en la ciencia ni en la religión. Así mismo, la cuestión central del diálogo entre ambos dominios se ubica en la pregunta por el origen del sentido. La segunda parte critica el presupuesto de las teorías socioconstruccionistas, según el cual todo sentido es enteramente un producto humano. Finalmente, se señalan algunos aspectos sobre los cuales las ciencias y el cristianismo pueden dialogar acerca de la existencia de un sentido trascendente en la naturaleza y la vida humana. © 2018.